Stop bands in magneto-photonic crystal in millimeter waveband - Khodzitsky, M.K. (Радіофізика та електроніка, 2009)
One-dimensional (1D) magneto-photonic crystal (MPC) with tri-layer cell (vacuum-ferrite-quartz) interfaced with wire medium (WM) was investigated at microwave band. The appearance of two stopbands associated correspondingly with wave interference in the MPC and with ferromagnetic resonance absorption in ferrite layer was demonstrated. The occurrence of surface waves for the MPC+WM system in the MPC stop band frequency range was shown theoretically and experimentally. The surface wave peak allows the tuning of its position with applied magnetic field. It was shown that the steepness of the curve describing the dependence of surface wave peak position on magnetic field is less than the steepness of the corresponding curve for the left edge of the MPC stop band. The considered effects will make it possible to develop new magneto tunable microwave devices on basis of magneto-photonic crystals for GHz and THz band.